SUPLEMENTASI RDP (RUMEN DEGRADABLE PROTEIN) DAN UDP (UNDEGRADABLE PROTEIN) DALAM RANSUM DOMBA TERHADAP DEGRADASI BAHAN KERING DAN BAHAN ORGANIK DALAM RUMEN SECARA IN VITRO - Iswanto, Dimas Oqi Nur; Rimbawanto, Efka Aris; Bata, Muhamad (ANGON: Journal of Animal Science and Technology, 2022)
Background. Research "Supplementation of RDP (Rumen Degradable Protein) and UDP (Undegradable Protein) in Sheep Ration on In Vitro Degradation of Dry Matter and Organic Matter in Rumen". This study aims was determine the effect of RDP and UDP supplementation in sheep rations on dry matter degradation and in vitro organic matter degradation. Materials and methods The research material used were the rumen fluid of 3 sheep as a source of inoculum, treatment rations supplemented with RDP (urea-zeolite) and UDP (soybean meal protected by condensation tannins). The in vitro research method used a completely randomized design (CRD) with 5 treatments and 5 replications. The treatments tested were R1 = basal ration (30% elephant grass silage, 70% concentrate) + 1% RDP and 1% UDP; R2 = basal ration + RDP 1% and UDP 2% ; R3 = basal ration + RDP 1% and UDP 3% ; R4 = basal ration + RDP 2% and UDP 1% ; R5 = basal ration + RDP 3% and UDP 1%. The variables measured were dry matter degradation and organic matter degradation at 48 hours incubation. Results. The results showed that supplementation of RDP and UDP in sheep rations had no significant effect (P>0.05) on the value of dry matter and organic matter degradation. Conclusion. It can be concluded that the administration of RDP and UDP supplementation in sheep rations in vitro did not interfere with rumen microbial activity